Navigating the quantum future: Legal perspectives from the united states and saudi arabia - Jarri, Fatema Al; Alshayib, Rawan; Alrakah, Arwa; Ali, Layan Al; Alshayeb, Sara; Nagy, Naya (Institute Of computer Science (IOCS), 2024)
Quantum computing (QC) is emerging as a transformative technology with the potential to revolutionize computation and surpass classical computers in more aspects. However, this power presents unique legal challenges and cybersecurity threats that need to be considered. This article critically examines the legal frameworks governing Quantum computing in the United States and Saudi Arabia. It discuss the recent research, discoveries, and partnerships in the QC landscape employed in Saudi Arabia and the future. It evaluates how current regulations in Saudi Arabia address emerging technologies like QC and contrasts them with US federal law. Furthermore, this article explores the potential legal challenges posed by QC advancements. It proposes adjustments to existing regulations to include quantum considerations. The findings suggest that although both countries have robust cybersecurity frameworks, proactive measures like updating intellectual property rights and data protection laws are essential for navigating this technological revolution